Synesthetic Approach in the Design Process for Enhanced Creativity and Multisensory Experiences. (28th July 2017) - Merter, Sevi
Abstract: Synesthesia –involuntary cross-modal sensory associations– is in very close relationship with perception, creativity, and imagination. Since design appeals to senses and provides multisensory experiences to users, synesthesia can be developed as a multisensory design method and framework –a multisensory instrument– having the potential to change the perception of the practice and the embodiment of a design idea accordingly. It can prompt creativity and imagination as well as enhancing the user experience and interaction with the product. Within this perspective, this paper aims to suggest a new territory for design research by investigating the relationship among synesthesia, creativity, and perception in order to contextualize the association between synesthesia and design and presenting a few exemplary designs that are found inspirational within the context. Then, synesthetic approach as a design method and framework is proposed with the intention to utilize and provide unique and intersubjective experiences in the field of product design.